MO408: Hepatic Steatosis in Patients With Type 2 Diabetes and Chronic Kidney Disease. (3rd May 2022) - Adrian, Therese; Hornum, Mads; K. Knop, Filip; Peter Almdal, Thomas; Rossing, Peter; Lida, Lisa; Søndergaard Heinrich, Niels; Boer, Vincent; Marsman, Anouk; Petersen, Esben; Siebner, Hartwig; Feldt-Rasmussen, Bo
Abstract: BACKGROUND AND AIMS: Non-alcoholic fatty liver disease (NAFLD) is suggested as being a risk factor for chronic kidney disease (CKD). The incidence of NAFLD is rising globally parallel to the increasing incidences of obesity and type 2 diabetes. As diabetes remains the leading cause of CKD the co-existence of NAFLD, CKD and type 2 diabetes needs to be explored. Here, we evaluated the prevalence of hepatic steatosis in patients with type 2 diabetes and CKD and patients with type 2 diabetes without CKD. METHOD: This cross-sectional study included 50 patients with type 2 diabetes and CKD stages 3–5 and 50 patients with type 2 diabetes without CKD. Liver fat content was estimated by proton magnetic resonance spectroscopy (1H-MRS) and magnetic resonance imaging proton density fat fraction (MRI-PDFF) by the multi-echo Dixon-technique in a 3 Tesla full-body MRI scanner. Hepatic steatosis was defined as ≥ 5.56% liver fat. Further, continuous glucose monitoring (CGM) was performed for 4 days. RESULTS: Mean age 72.0 ± 4.9 years and body mass index (BMI) 28.6 ± 3.5 kg/m 2 in patients with CKD, and mean age 65.9 ± 7.8 years and BMI 27.0 ± 4.0 kg/m 2 in patients without CKD with a predominance of men in both groups. Hepatic steatosis was identified in 22 (44%) patients with CKD and 19 (38%) patients without CKD (P = 0.68). Median (IQR) values of percentage liver fat were 4.7% (3.0–8.5) and 4.1% (2.9–7.7) in patients with and without CKD, respectively, corresponding to 5.3% higher levels of hepatic fat percentage in patients with CKD [95% confidence interval (CI) −23; 45, P = 0.75]. Mean sensor glucose from CGM was 9.0 ± 1.6 mmol/L and 8.7 ± 1.8 mmol/L in patients with and without CKD, respectively (P = 0.47). There was no statistically significant difference between the two groups regarding the percentage of time spent in different CGM ranges: time-below-range, <3.9 mmol/L (P = 0.83), time-in-target-range, 3.9–10.0 mmol/L (P = 0.20) and time-above-range, >10.0 mmol/L (P = 0.20). Pooled data from both groups showed no significant association between the mean sensor glucose from CGM and hepatic fat percentages (P = 0.38). CONCLUSION: These findings do not support any association between hepatic steatosis and CKD stages 3–5 in patients with type 2 diabetes.